1989
DOI: 10.1002/ajpa.1330320506
|View full text |Cite
|
Sign up to set email alerts
|

Female choice in nonhuman primates

Abstract: As outlined by Darwin, sexual selection is composed of two parts, within-sex competition for mates, and mate choice. The fact that males compete for fertile females has been well established. More equivocal is the notion that females have preferences for certain males, and that those preferences have a n evolutionary effect (''female choice"). We now have a n evolutionary framework and sophisticated mathematical models to evaluate female choice. A review of the literature on primate species reveals that 20 spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(53 citation statements)
references
References 80 publications
1
51
0
1
Order By: Relevance
“…Females thus did not have the opportunity to express a preference for unfamiliar or novel males, as observed in other primate species (e.g. Bercovitch, 1997;Perei ra and Weiss, 1991;Small, 1989). However, in a detailed study of mate preference in rhesus macaques, Manson (1995) concluded that his data provided "at most, weak support for the hypothesis that female primates in multi-male groups exercise mate choice for novel males" (p. 285).…”
Section: Limitations Of the Studymentioning
confidence: 91%
“…Females thus did not have the opportunity to express a preference for unfamiliar or novel males, as observed in other primate species (e.g. Bercovitch, 1997;Perei ra and Weiss, 1991;Small, 1989). However, in a detailed study of mate preference in rhesus macaques, Manson (1995) concluded that his data provided "at most, weak support for the hypothesis that female primates in multi-male groups exercise mate choice for novel males" (p. 285).…”
Section: Limitations Of the Studymentioning
confidence: 91%
“…Thus, just as the costs of producing infants drive mate selectivity by females (Small 1992), the costs of competition and mate guarding should drive a certain degree of selectivity by males. Males may be expected to invest more intensively in mates that have the highest probability of conceiving and raising offspring successfully.…”
Section: How Do Costs Of Mating Effort Influence Male Mating Tactics?mentioning
confidence: 99%
“…The role of mate choice in the evolution of sexual dimorphism in primates has received less attention than mate competition. Recent years have seen an increase in the literature discussing female mating strategies (e.g., Small, 1989;Smuts and Smuts, 1993;Nunn, 1999;van Schaik et al, 1999;Stallmann and Froehlich, 2000). These involve explicit female choice, as well as various female strategies to counter male mating coercion and domination (Smuts and Smuts, 1993).…”
Section: Sperm Competitionmentioning
confidence: 99%
“…It is widely hypothesized that females in multimale groups mate polyandrously in order to confuse paternity (e.g., Small, 1989;Smuts and Smuts, 1993;Pagel, 1994;Nunn, 1999;van Schaik et al, 1999;Stallmann and Froehlich, 2000). Females in single-male groups are known to seek out "sneak" matings with extragroup males.…”
Section: Sperm Competitionmentioning
confidence: 99%